Duration of complex-spikes grades Purkinje cell plasticity and cerebellar motor learning - Yang, Yan (2014)
Behavioral learning is mediated by cellular plasticity such as changes in the strength of synapses at specific sites in neural circuits. The theory of cerebellar motor learning(1,2,3) relies on movement errors signaled by climbing-fiber inputs to cause long-term depression of synapses from parallel fibers to Purkinje cells(4,5). Yet, a recent review(6) has called into question the widely-held view that the climbing fiber input is an “all-or-none” event. In anesthetized animals, there is wide variation in the duration of the complex-spike (CS) caused in Purkinje cells by a climbing fiber input(7). Further, the duration of electrically-controlled bursts in climbing fibers grades the amount of plasticity in Purkinje cells(8,9). The duration of bursts depends on the “state” of the inferior olive and therefore could be correlated across climbing fibers(8,10). Here, we provide a potential functional context for these mechanisms during motor learning in behaving monkeys. The magnitudes of both plasticity and motor learning depend on the duration of the CS responses. Further, the duration of CS responses appears to be a meaningful signal that is correlated across the Purkinje cell population during motor learning. We suggest that during learning, longer bursts in climbing fibers lead to longer duration CS responses in Purkinje cells, more calcium entry into Purkinje cells, larger synaptic depression, and stronger learning. The same graded impact of instructive signals for plasticity and learning could occur throughout the nervous system.